2008
DOI: 10.1080/01904160802403102
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Nitrogen Application Methodology Impacts on Corn Grain Yield

Abstract: Increased fuels costs have prompted many producers to consider conservation tillage techniques and single pass applications of nitrogen (N) fertilizer and herbicide to reduce fuel expenses. The objective of this study was to determine the impacts of tillage and nitrogen application methodology on corn grain yield. The experiment was conducted from 2002-2005 at the Northwest Research Station of the Ohio Agricultural Research and Development Center (OARDC) near Hoytville, OH. Six different tillage regimes were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…However, the most detrimental effect on corn yield may have been a drought period in June of 2008 and 2009 when corn was pollinating and most sensitive to water stress. This is in agreement with reports that mid-season water deficits would override the effect of N, even in a short duration (Strachan et al, 2002) and dry conditions during a growing season could result in low corn yield (Viswakumar et al, 2008;Haghighi et al, 2010), especially drought during silking period. Kim et al (2008) also noted that the amount of N fertilizer needed to produce a unit of grain yield is related to the yield loss due to water stress.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the most detrimental effect on corn yield may have been a drought period in June of 2008 and 2009 when corn was pollinating and most sensitive to water stress. This is in agreement with reports that mid-season water deficits would override the effect of N, even in a short duration (Strachan et al, 2002) and dry conditions during a growing season could result in low corn yield (Viswakumar et al, 2008;Haghighi et al, 2010), especially drought during silking period. Kim et al (2008) also noted that the amount of N fertilizer needed to produce a unit of grain yield is related to the yield loss due to water stress.…”
Section: Discussionsupporting
confidence: 82%
“…The effect of N application time on yield is not conclusive in the literature. Some researchers have reported that corn yield increased with split or sidedress N applications (Gehl et al, 2005;and Viswakumar et al, 2008), but others reported no yield difference between the two application methods in some years due to dry conditions throughout the growing season (Viswakumar et al, 2008), or reduced yield with split N applications (Randall et al, 1997). In our study, insufficient precipitation might be the reason for no yield difference between N applied at planting and through split applications.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Insufficient water availability during the corn reproductive silking stage, which is the most critical stage, most likely contributed to reduced yields. Haghighi et al (2010) and Viswakumar et al (2008) reported very poor corn yields under dry conditions due to insufficient rainfall and little response to N application. Kiziloglu et al (2009) observed a linear relationship between water use efficiency and corn grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…The lower relative efficiency of UAN Spring compared with AA Spring could be explained by the presence of nitrate in UAN (25% of total N) that can be easily lost with rainfall immediately after spring applications, and the presence of urea in UAN that can be lost by volatilization if it is applied on the soil surface, and because urea converts to nitrate much more rapidly than AA. Another reason for lower relative efficiency of UAN is that many growers try to reduce the cost of application by using weed‐and‐feed spring N applications (before or immediately after planting), where a large portion of the total N is broadcast with herbicides on the soil surface; therefore, this N is more likely to be lost by volatilization or leaching (Viswakumar et al, 2008).…”
Section: Resultsmentioning
confidence: 99%